UNVEILING THE CURIOSITY CURRENT: A STUDY OF STEM ENGAGEMENT AMONG COASTAL SCHOOL STUDENTS IN SEMPORNA, SABAH - Jamilah Ahmad; Almasiah Hassan; Yusmail Jusup (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This cross-sectional study investigates curiosity levels toward STEM among 185 coastal school students aged 10 to 12 in Semporna, Sabah. With the aim of emphasizing the importance of STEM education in shaping future professionals and addressing global challenges, the research seeks to stimulate curiosity and encourage young learners to actively participate in their surroundings. Using a descriptive survey questionnaire design, the study employs the Curiosity Towards STEM instrument, assessing two constructs—Exploration and Acceptance—with a total of ten items. The research focuses on evaluating the level and extent of curiosity among respondents regarding STEM. Results reveal a significant level of curiosity toward STEM in both exploration and acceptance among coastal school students. Interviews with a focus group shed light on how curiosity contributes to knowledge expansion, improved critical thinking, creativity, reduced fear of failure, enhanced self-confidence, and the joy of discovery. These findings underscore the high potential of students in coastal school areas for excelling in STEM subjects. However, challenges such as resource limitations, cultural influences, socioeconomic factors, and logistical issues impact the manifestation of curiosity, highlighting the need for tailored interventions to nurture curiosity effectively in these unique educational settings.